Sponsorship sales in minor sport : the 2013 International Triathlon Union World Duathlon Championships - O'Reilly, Norm, 1973-; Gattinger, Alana; Beselt, Elisa (London : Human Kinetics, Inc., 2014)
This case focuses on the sponsorship sales aspect of the 2013 International Triathlon Union World Duathlon Championships in Ottawa, Ontario, Canada. The case outlines the process of acquiring the right to host the event and creating/implementing a sponsorship sales strategy for the event. The case provides background on the sport of duathlon and the city of Ottawa's capacity to host an international sport event of this level. This case recognizes that securing sponsorship is a major challenge that many small sport organizations and sport events face. Strategies are presented to show how these sport organizations can actively promote their offerings to overcome this challenge. Intended for graduate and undergraduate students in sport management, event management, and marketing, information for this case was obtained from interviews with event staff, secondary research, and documentation provided by the event organizing committee. It will be necessary for students to use critical thinking to provide feedback to the organizing committee about how they can target and acquire sponsors for the 2013 International Triathlon Union World Duathlon Championships.
Originally published in O'Reilly, N., Gattinger, A., & Beselt, E. (2014). Sponsorship sales in minor sport: The 2013 International Triathlon Union World Duathlon Championships. Case Studies in Sport Management, 3(1), 93-104. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; International Triathlon Union World Duathlon Championship; Sports sponsorship -- Ontario -- Ottawa; Special events -- Ontario -- Ottawa -- Management